Dietary changes and sleep procrastination among university professors and students during the COVID-19 pandemic (Research, Society and Development, 2022)
Objective: To understand the relationship between food during the COVID-19 pandemic and sleep procrastination among teachers and students. Methodology: Cross-sectional study, professors and students of a State University of Bahia (n=495). The population was invited to participate in the research through virtual means (email and social networks), and they were asked if they had any influence on the weight and consumption of food groups during social distancing. The habit of procrastinating or bedtime was assessed using the Bedtime Procrastination Scale. To assess the pattern of sleep procrastination, Exploratory Factor Analysis was used with the principal component analysis technique. For Data statistics used up Sta Software Version 12.0. Results: During social distancing in COVID-19, it can be observed that university students who procrastinated sleep had higher consumption of fast foods (PR= 1.68 95%CI = 1.14-2.49), when compared to who slept at the right time (PR= 0.87 95%CI = 0.82-1.08). Conclusion: The university results show an increase in total food intake and consumption of fast food with difficulties in starting sleep and an increase in the rate of procrastination at the time of professors and students.